A COMPARISON STUDY OF TECHNICAL TRAINING MODEL IN MINI GAME PERFORMANCE, SPEED AND ACCURACY AMONG BASKETBALL PLAYERS - Singh, Dr. Prince Inder; Kaur, Dilpreet; Kadam, Dr. Govind K.; Kadam, Dr. Kamlakar K. (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The study investigated the effect of teaching match Games for Understanding coaching approach on university men basketball players as they have problem in term of speed and accuracy executing general basketball skills, ball control, decision making, skill execution with players on the ball, as well as supporting player’s role without ball in 5 versus 5 mini game situations. The study was a quasi-experimental equivalent pretest-posttest groups design whereby sports on university level basketball women players (19-22years old) randomly assigned to experimental groups of (n= 15), and control group (n=15). The training model was exposed to tactical coaching approach, while the control group underwent predominantly skill-based coaching in Basketball. The effectiveness of these two models was measured standardized basketball test, and Game observation Instrument. Univariate of ANOVA was used to analyze the data, followed with analysis of covariance (ANCOVA) if the pretest results yielded significant difference. The results indicated that there were significant difference between experimental and control group posttest score on speed (1, 28) =15.25, p<0.05, and in ball control, 5 versus 5 game play F (1, 28) =3.34, p<0.05.